Effect of Storage Time of Fermented Milk Using Lactiplantibacillus plantarum SN13T on Fermented Milk Quality - Auliarasulina, Siti; Melia, Sri; Juliyarsi, Indri (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
Storage of fermented milk is esseential to maintain its quality, safety, and probiotic benefits.  This study aimed to evaluate the effect of storage duration on fermented milk using Lactiplantibacillus plantarum SN13T starter for 30 d at refrigerator temperature (4°C) on the quality of fermented milk.  Key parameters assessed included moisture content, protein content, fat content, pH, titrable acidity, total lactic acid bacteria (LAB), viscosity, water holding capacity, syneresis, and organoleptic properties.  The treatment in this study was the length of storage of L. plantarum SN13T fermented milk, namely 0 d (A), 10 d (B), 20 d (C), and 30 d (D).  The results showed that after 30 d of fermented milk storage at refrigerator temperature using L. plantarum SN13T starter had a water content of 89.32%, protein content of 0.74%, fat content of 2.41%, pH 4.32, titrable acidity of 1.39%, and total lactic acid bacteria count of 1.55x 109 CFU/ml.  Viscosity was 1137.00 Pa-s, water holding capacity 50.91%, and syneresis 38.85%.  The organoleptic evaluation showed that color, taste, texture, and aroma remained favorable for up to 30 d of storage.  These findings conclude that fermented milk stored for up to 30 d using L. plantarum SN13T starter meets Codex and Indonesian National Standards for safety and quality.  This fermented milk drink is suitable for use as a health drink because it contains probiotic L. plantarum SN13T.